A biographical experience of teacher education in Aotearoa New Zealand. Issue 5 (20th October 2017) - O'Neill, John
Abstract: The article analyses initial teacher education (ITE) policy and practice in Aotearoa New Zealand over forty years. Central to the local ITE context was the incorporation of the 'monotechnic' colleges of teacher education into the university sector in the 1990s and 2000s, following New Zealand's structural adjustments to the state education sector in 1989 and 1990. Policy ideologies of 'marketisation' and 'professionalisation' raised expectations of the abstract knowledge base and competencies that university-based teacher education graduates would acquire, while simultaneously degrading the rich immersion in cultural, curriculum and subject studies and learning by doing that were the hallmark of the former colleges. Indigenous staff and students arguably suffered most during the incorporation years. The final section looks to New Zealand's future demographic, environmental and socio-economic imperatives and asks how ITE can be recast to enable teacher educators and beginning teachers to face the realities and challenges of the decades ahead.